The relationship between the financial crisis and the measurement of fair value in financial statements - Gudonytė, Birutė; Rudžionienė, Kristina (Buhalterinės apskaitos teorija ir praktika, 2014)
Literature suggests that the main goal of fair value evaluation is more reliable and relevant information disclosure to external users. However, in 2007, at the beginning of the global financial crisis, the benefits of fair value, as well as the opportunity to provide information about the true and fair view of a company, were called into question. Opponents of the fair value claim that the fair value was the main reason for the global financial crisis, but the advocates disagree; therefore, the correlation between the fair value and crisis is controversial. It reflects the problem of the thesis: how the system of fair value accounting influenced the financial crisis? Object of the paper: the method of true value measurement. Aim of the paper: to evaluate the measurement of fair value and its potential impact on the financial crisis in Lithuania. After analysing the evaluation of 25 Lithuanian listed companies by disclosure of fair value, it can be state that stock companies evaluate more property than liabilities by disclose the fair value. A correlation coefficient was determined while assessing the correlation between the application of fair value in financial reports and financial crisis in Lithuania, but it disapproved the correlation.